Answer:
Therefore the solution set is (x , y) = ( 2 , 1 )
Step-by-step explanation:
Given:
[tex]-2x+y=-3[/tex] ...............Equation ( 1 )
[tex]x+y=3\\[/tex] ...............Equation ( 2 )
[tex]\therefore y=3-x[/tex] ...............Equation ( 3 )
To Find:
x = ?
y = ?
Solution:
Using Substitution Method we will have
Substitute above ' y ' Equation 3 in Equation 1 we get
[tex]-2x+(3-x)=-3\\-2x-x=-3-3\\-3x=-6\\3x=6\\x=\dfrac{6}{3}=2\\\\x=2[/tex]
Now Substitute ' x ' in Equation 3 we get
[tex]y=3-2=1\\y=1[/tex]
Therefore the solution set is (x , y) = ( 2 , 1 )